Analisis Indeks Masa Tubuh Berbasis Citra Digital Menggunakan Metode Body Surface Area - Umy Habibah, Nurina; Rosyady, Phisca Aditya; Pribadi, Riski Pribadi (Website, 2023)
Measuring human weight and height in the modern era is still using the old method, namely using manual measuring tools such as digital scales to measure body weight and stature meters to measure height and are done separately so that it takes quite a long time if done by many users and repeatedly – such as for the purposes of administering medical personnel and recruiting military agencies. Therefore, in this study, measurements of human weight and height were carried out simultaneously in one system using the body surface area method and morphological operations in digital images as image enhancements. The process begins with the input image in the form of a human photo with a white background and full body with the human facing the front of the camera straight and the distance between the human and the cellphone camera is 2 meters and the height of the camera and the floor is 1.5 meters, after that the resulting photo will be subjected to object segmentation or preprocessing. by counting the number of pixels from toe to head to find out the value of height, meanwhile, to calculate body weight, the area of the human body is calculated in pixels and one photo is used to get the reference data value. Based on the results of testing the tools that have been made, it can be concluded that this system can produce measurements of maximum height with an accuracy of 99.15% and maximum weight with an accuracy of 97.35% with a photo resolution of 12 mega pixels with details of a photo height of 2080 px and a photo width 4624 px of height and weight data can then be processed to find out the body mass index value, which determines the ideal human body. Keywords: Matlab, Image Processing, Body Mass Index, Body Suface Area